He thought, she thought: The importance of subjective patterns to understanding team processes. (7th July 2016) - Emich, Kyle J.; Lu, Li
Summary: Teams are often described using the mean and variance of their member's characteristics. Recently, research has advanced this paradigm by beginning to explore the importance of patterns of team member perceptions regarding themselves, their teammates, and their teams. We highlight this work and suggest several directions for future research. Copyright © 2016 John Wiley & Sons, Ltd.